2021
DOI: 10.1111/ajt.16501
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 in pediatric kidney transplantation: The Improving Renal Outcomes Collaborative

Abstract: There are limited data on the impact of COVID‐19 in children with a kidney transplant (KT). We conducted a prospective cohort study through the Improving Renal Outcomes Collaborative (IROC) to collect clinical outcome data about COVID‐19 in pediatric KT patients. Twenty‐two IROC centers that care for 2732 patients submitted testing and outcomes data for 281 patients tested for SARS‐CoV‐2 by PCR. Testing indications included symptoms and/or potential exposures to COVID‐19 ( N = 134, 47.7%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 27 publications
(30 reference statements)
2
57
1
1
Order By: Relevance
“…However, testing for the virus was not widely performed in this cohort and only three patients had a positive PCR test [13]. Another study which included 24 patients identified from 22 centers in the USA, demonstrated an overall incidence of COVID-19 of 0.6% in pediatric KTRs [14]. Other studies were not able to estimate the incidence of COVID-19 in pediatric kidney disease, due to under-reporting of milder cases and asymptomatic patients who never presented to healthcare units [15].…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…However, testing for the virus was not widely performed in this cohort and only three patients had a positive PCR test [13]. Another study which included 24 patients identified from 22 centers in the USA, demonstrated an overall incidence of COVID-19 of 0.6% in pediatric KTRs [14]. Other studies were not able to estimate the incidence of COVID-19 in pediatric kidney disease, due to under-reporting of milder cases and asymptomatic patients who never presented to healthcare units [15].…”
Section: Discussionmentioning
confidence: 87%
“…One multicenter study reported eight pediatric KTRs with COVID-19, all of whom had mild disease although two were hospitalized [19]. Another multicenter study identified 24 pediatric KTRs with COVID-19, eight were hospitalized and two were admitted to the ICU [14]. A study from 30 countries described 113 pediatric KTRs and children on immunosuppressive medication for kidney disease who were diagnosed with COVID-19 [15].…”
Section: Discussionmentioning
confidence: 99%
“…The disease incidence among our pediatric SOT patients was considerably higher than the incidence previously reported among pediatric kidney recipients. 6 This difference may be due to the high population density and family crowding in certain Israeli cities and communities. During the acute phase of COVID-19 infection, 23 (92%) of our patients were symptomatic.…”
Section: Discussionmentioning
confidence: 99%
“…Two patients in that cohort experienced transient acute kidney injury and another two patients had biopsy confirmed acute rejection, and were treated per institutional protocols without reduction of immunosuppression. 15 In our case, due to the symptomatic COVID-19 infection with desaturations, concern for pneumonia, and severe allograft dysfunction, we opted for an overall reduction of immunosuppression by withholding mycophenolate mofetil and postponing active antibody-mediated rejection treatment other than intravenous immunoglobulin, along with systemic anti-inflammatory with intravenous methylprednisolone. This proved effective in preserving allograft function and reversing the acute nephrosis.…”
Section: A S E Rep Ortmentioning
confidence: 99%